An Introduction to pain and its relations to nervous system disorders - 4 0 16; Battaglia, Anna A.; 5 Ohio Library and Information Network (Chichester, West Sussex ;;Hoboken, NJ : John Wiley & Sons Inc., 2016)
Introduction to Pain and its relations to Nervous System Disorders provides an accessible overview of the latest developments in the science underpinning pain research, including, but not limited to, the physiological, pathological and psychological aspects. This unique book fills a gap in current literature by focussing on the intricate relationship between pain and human nervous system disorders such as Autism, Alzheimer Disease, Parkinson's Disease, Depression and Multiple Sclerosis. This fully illustrated, colour handbook will help non-experts, including advanced undergraduate and new postgraduate students, become familiar with the current, wide-ranging areas of research that cover every aspect of the field from chronic and inflammatory pain to neuropathic pain and biopsychosocial models of pain, functional imaging and genetics. Contributions from leading experts in neuroscience and psychiatry provide both factual information and critical points of view on their approach and the theoretical framework behind their choices. An appreciation of the strengths and weaknesses of brain imaging technology applied to pain research in humans provides the tools required to understand current cutting edge literature on the topic. Chapters covering placebo effects in analgesia and the psychology of pain give a thorough overview of cognitive, psychological and social influences on pain perception. Sections exploring pain in the lifecycle and in relation to nervous system disorders take particular relevance from a clinical point of view. Furthermore, an intellectually stimulating chapter analysing the co-morbidity of pain and depression provides a philosophical angle rarely presented in related handbooks. The references to external research databases and relevant websites aim to prompt readers to become critical and independent thinkers, and motivate them to carry out further reading on these topics. Introduction to Pain and its relations to Nervous System Disorders is essential reading for advanced undergraduate and postgraduate students in neuroscience, medical and biomedical sciences, as well as for clinical and medical healthcare professionals involved in pain management--;Provides an accessible overview of the latest developments in the science underpinning pain research--
Includes index.
Keywords: 2 -- 0; 6; Research.;Diseases. -- Pain;Nervous system -- 2; 20; Electronic books. -- 2